2023
DOI: 10.1186/s13019-023-02215-3
|View full text |Cite
|
Sign up to set email alerts
|

One-stage VATS surgery for synchronous bilateral lung lesion: a safe and feasible procedure

Abstract: Background Synchronous bilateral lung lesions are emerging as a common but tricky disease for surgical management. Whether one or two-stage surgery should be taken remains in debate. We retrospectively analysed 151 patients who underwent one and two-stage Video Assisted Thoracic Surgery (VATS) to investigate the safety and feasibility of the two surgical approaches. Methods A total of 151 patients were included in the study. Propensity score matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Given the intricacies of thoracic surgery, unilateral procedures have traditionally been favored in clinical practice; however, recent evidence challenges this notion. A study involving 151 patients demonstrated that for individuals without relevant risk factors, bilateral surgeries do not result in increased severity or complications [36], there is a greater body of literature available to substantiate this conclusion [37,38]. However, further controlled trials are still required to substantiate this conclusion.…”
Section: Multiple Ground-glass Nodules Are Observed In the Bilateral ...mentioning
confidence: 99%
“…Given the intricacies of thoracic surgery, unilateral procedures have traditionally been favored in clinical practice; however, recent evidence challenges this notion. A study involving 151 patients demonstrated that for individuals without relevant risk factors, bilateral surgeries do not result in increased severity or complications [36], there is a greater body of literature available to substantiate this conclusion [37,38]. However, further controlled trials are still required to substantiate this conclusion.…”
Section: Multiple Ground-glass Nodules Are Observed In the Bilateral ...mentioning
confidence: 99%